Feelings, Thoughts and Experiences of Caregivers of Individuals with Substance Use Disorder - Mahperi Uluyol, Fatma; Bademli, Kerime (Addicta: The Turkish Journal on Addictions, 2020)
This qualitative study was carried out to determine the burden of care on Turkish caregivers of patients with substance use disorder. The sample included relatives of 42 patients hospitalized in the Akdeniz University Alcohol and Drug Addiction Research and Application Center. Individual in-depth, open semi-structured interviews were used for data collection. Moreover, demographic questions and an interview guide with questions were also used. According to the results of this study, the following themes were evaluated: difficulties experienced, coping, and needs. The findings showed that substance abuse has adverse consequences and negatively affects both the patients and their relatives in terms of economic, psychological, and social aspects. Furthermore, because of the social stigma of substance abuse, the families receive very limited social support from the environment. This weakens the well-being of the family members and increases intrafamily conflicts. We conclude that ensuring the well-being of the caregivers of patients with substance use disorder is useful in maintaining a successful treatment of addiction. Thus, policymakers should include the relatives of patients with substance use disorder in prevention and intervention programs to increase the effectiveness of the interventions.
Keywords: Caregiver; addiction; family experience; substance use disorder; coping skill